2000
DOI: 10.1038/sj.bdj.4800859
|View full text |Cite
|
Sign up to set email alerts
|

Microbial aerosols in general dental practice

Abstract: The data have been used to generate a framework for quantifying risk of exposure of staff to aerosolised microbial pathogens in general dental practice. For example, dentists and their assistants may have a slightly higher risk of exposure to Mycobacterium tuberculosis than the general public. The use of face seal masks that have been shown to protect against aerosolised micro-organisms may reduce this exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 17 publications
2
76
0
1
Order By: Relevance
“…Since these droplets can remain airborne for as much as 30 min after the dental procedures, they can easily reach the respiratory system (Logothetis and Martinez-Welles 1995). Water in the largest airborne droplets can evaporate, leaving smaller particles (droplet nuclei) that may carry respiratory bacteria (Bennett et al 2000). Other studies found that the levels of airborne bacterial pollution inside the dental room were elevated much higher than background during the use of dental procedures (Legnani et al 1994).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since these droplets can remain airborne for as much as 30 min after the dental procedures, they can easily reach the respiratory system (Logothetis and Martinez-Welles 1995). Water in the largest airborne droplets can evaporate, leaving smaller particles (droplet nuclei) that may carry respiratory bacteria (Bennett et al 2000). Other studies found that the levels of airborne bacterial pollution inside the dental room were elevated much higher than background during the use of dental procedures (Legnani et al 1994).…”
Section: Introductionmentioning
confidence: 96%
“…A study that examined the production of particles from the dental activities concluded that the use of antiseptic solutions such as the 0.12% chlorhexidine gluconate can prevent the formation of viable bacteria aerosol (Logothetis and Martinez-Welles 1995). In another study, occasional (higher than background) concentrations of presumptive oral streptococci were associated with mechanical scaling and cavity preparation (Bennett et al 2000). This paper describes the first systematic measurements of particle number, size, mass concentrations, and elemental composition of the particles in a dental office during dental drilling procedures associated with fillings and crowns.…”
Section: Introductionmentioning
confidence: 96%
“…Aerosols in a dental office can be generated by procedures involved with instruments (e.g., low-speed handheld implements, ultrasonic scalers, bicarbonate polishers, and drilling and air sprays inside the oral activity). [10,11] Studies have provided evidence [12,13] that aerosols, consisting of moisture droplets and particulate matter (PM), are associated with mechanical scaling and cavity preparation, particularly the aerosols generated by high-speed dental equipment that were 5 mm or less in diameter. [12] Dental grinding has been reported to yield the highest submicrometer particle concentrations on average 16 times higher than the indoor background.…”
Section: Introductionmentioning
confidence: 99%
“…DUWL output water is also aerosolised by several dynamic dental instruments including conventional and high-speed handpieces and ultrasonic and air scalers and subsequently inhaled by patients and dental staff (Fotos et al ., 1985 ;Reinthaler et al ., 1988 ;Pankhurst and PhilpottHoward, 1993 ;Pankhurst et al ., 1998 ;Bennett et al ., 2000 ;Pankhurst, 2003 ;Wirthlin et al ., 2003 ;Szyma ń ska and Dutkiewicz, 2008 ; Decontamination in hospitals and healthcare Coleman et al ., 2009 ). These bioaerosols can persist in the air in the dental clinic for at least an hour before settling out.…”
Section: Narrow Bore Duwls and Laminar Fl Owmentioning
confidence: 94%